Stress-strain calculation and fatigue life assessment of V-shaped notches of turbine disk alloys. (December 2019) - Zhu, Shun-Peng; Xu, Shen; Hao, Meng-Fei; Liao, Ding; Wang, Qingyuan
Abstract: For local stress-strain behavior modeling at the notch root, both the Neuber's rule and equivalent strain energy density (ESED) method are commonly utilized in engineering practice, in which the former overestimates notch elasto-plastic responses while the latter gives conservative predictions. In this work, a correction coefficient related to the effective Poisson's ratio v eff is proposed to quantify the weight of dissipated heat energy term with the modified ESED model. Notch-root strains predicted by the proposed model are compared with nonlinear FE calculations of GH4169 and TC4 V-shaped notched-bars, in which the proposed solution provides good agreement with FE results for both cases. Then, consulting the idea of local stress-strain approaches, a fatigue lifing model is derived assuming that the notched specimens fail once reach the critical total strain energy as same as that of smooth ones. Results indicated that prediction accuracy of local equivalent strains at notch roots is improved, and yields better life predictions than the Ellyin's model for the two alloys. Highlights: A proposed solution to quantify the weight of heat energy term based on the modified ESED method. Better correlations between the proposed model predictions and FEA results for TC4 and GH4169 alloys. A modified energy-based model for life prediction considering the notch support effect. Two types of V-shaped notch specimens with different K t for model validation.